The Role Model Method​​ in Learning Akidah Akhlak ​ for Grade VIII Students at Mts Darul Ulum Kembang Kuning​​ Central Amuntai District - Mera Wati; Ramlan Thalib; Ria Susanti (Integrated Education Journal, 2025)
This research is motivated by the fact that the Akidah Akhlak teacher has used the modeling method in learning, but still found moral crisis behavior among students such as lack of manners, ethics, respect, honesty, and responsibility. The purpose of this writing is to determine the use of the modeling method in learning Akidah Akhlak in class VIII students of MTs Darul Ulum Kembang Kuning, Amuntai Tengah District. The subject in this writing is one Akidah Akhlak teacher. The results of this writing show that the use of modeling methods in learning Akidah Akhlak in class VIII students at MTs Darul Ulum Kembang Kuning is that teachers use direct modeling methods (direct method) such as saying greetings, reading prayers, and reading surah al-Zalzalah, and indirect exemplary methods (indirect method) such as telling personal experiences and telling stories from figures. While the use of steps carried out by Akidah Akhlak teachers in using modeling methods during teaching and learning are showing religious practices, conveying material clearly, providing real examples both from personal experiences and from figures, asking questions, and encouraging students to provide examples. The supporting factors for the use of modeling methods in learning Akidah Akhlak are the role of the family, the role of teachers, and the existence of cooperation between schools and parents. While the inhibiting factors for the use of modeling methods in learning Akidah Akhlak are the lack of parental concern and student interaction, especially peers